Bluestar's acquisition of Adisseo. A - McFarlan, F. Warren (Franklin Warren); Donghong, Li; Zhenning, Yang ([London] : SAGE, 2016)
In early January 2006, Ren Jianxin, general manager of ChemChina sat in his office as the soft, warm winter sunshine passed through the window glass. A few days earlier, Bluestar had completed its acquisition of Adisseo in Brussels, Belgium. He was pleased that he had led Bluestar's management team in what had initially seemed impossible. A knock on the door interrupted his thoughts. It was his Administrative Assistant, informing him that the executive team was meeting to discuss matters post acquisition of Adisseo.
Originally Published in: McFarlan, F.W., Donghong, L., & Zhenning, Y. (2014). Bluestar's Acquisition of Adisseo (A). Beijing: Tsinghua SEM China Business Case Center.
Description based on online resource; title from home page (viewed on May 6, 2016).
Keywords: elektronické knihy; electronic books; Consolidation and merger of corporations -- Management -- Case studies